Control and ultra-short pulse generation in stimulated Raman backscattering. (March 2016) - Škorić, Miloš M.; Nikolić, Ljubomir; Hadžievski, Ljupčo; Batani, Dimitri; Ishiguro, Seiji; Mima, Kunioki
Abstract: A stimulated Raman scattering (SRS) is a great concern for laser fusion, causing an energy and symmetry loss and target preheating. In particular, for dominating backward- SRS (BRS), a complexity of nonlinear saturation was revealed. Recently, to develop lasers at multi-exawatts and beyond, relevant to high-energy physics, a proposed Raman amplification based on BRS met a restrictive operation window. Here, we stress BRS generics that due to a nonlinear frequency shift (relativistic/trapping effect), it nonlinearly saturates with intermittent pulsations. A "break up" of Manley-Rowe invariants explains a non-steady saturation. Further, a coherent pulsation BRS regime is proposed for femto-sec pulse generation in a thin exploding foil plasma, with parameter scalings investigated by analytics and particle simulations.